Sleep Deprivation Among Students - Iacovetti, Victoria; Marshall, Jeremy L. (My University, 2017)
Sleep deprivation is very common among college students, hitting 73% with sleep problems, according to “Regents of the University of Michigan.” To study the causes of sleep deprivation, I surveyed fifty students at Kansas State University, asking questions about the students’ sleep habits, class load and involvement with athletics, wondering if athletes and those with a heavy course load were more sleep deprived than those not involved in athletics and those with a lighter class schedule. My results showed a positive correlation between athlete involvement and sleep amount. However, I found no correlation between the amount of credit hours taken and whether or not people fall asleep in class. Sleep deprivation is often a result of over-scheduling with classes or being involved with sports or social activities. According to the National Sleep Foundation, with a minimal amount of sleep, this increases fatigue as well as energy and focus, whether it be school work or at game time.